Analisa Aliran Fluida pada Gas-Solid V Shaped Fluidized bed Reaktor dengan Computational Fluid Dynamics (CFD) - Sulistiyo, Raka Mahendra (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2023)
The use of gasification to deal with waste problems is an important issue of environmental conservation. One of the important components in the gasification system is the reactor design and one commonly used is the fluidized bed reactor. The use of a fluidized bed reactor requires solid particles in the form of powder. The V-shaped reactor design was used with laboratory scale sizes with variations in particle diameter, 0.3 mm, and 0.4 mm. Variations in the inlet gas velocity are 0.2 m/s, 0.3 m/s, 0.8 m/s. Computational Fluid Dynamic (CFD) simulation method in 2 dimensions is used to analyze the existing variables. With these variations, a fluid bed condition has occurred. Produced with a larger particle diameter tends to produce smaller bubbles. The inlet gas velocity of 0.2 m/s produces bigger bubbles than 0.3 m/s, while 0.8 m/s does not produce bubbles.